Radial Basis Function Artificial Neural Networks Can Predict UCP2 mRNA Levels According to Irisin Dose and Time of Application in the Cerebellum of Rats - Erden, Yavuz; Tekin, Suat; Colak, Cemil; Sandal, Suleyman; Tektemur, Ahmet; Onalan, Ebru Etem; Kirbag, Sevda (Wiley, 2015)
[Abstract Not Available]